Visual Perception Evaluation with Semantic Differentiation Method in Design Disciplines: Elazig Balakgazi Park - Cilek, Muge Unal (My University, 2023)
Visual perception studies in the public space are important in improving and developing any space’s design features. This study aims to evaluate landscape architects’ and architects’ visual perception of Balakgazi park design in the city of Elazig. Study methodology consists of four stages: (1) Determining the adjective pairs related to the feelings of pleasure, excitement, and dominance that are effective in evaluating the design; (2) preparation of visual perception questionnaires; (3) determination of visual perceptions with semantic differentiation technique (Likert scale); (4) MANOVA statistical analysis of the obtained data. In this study, the responses of 207 participants, 107 of them landscape architects and 98 architects, were evaluated. The data obtained from both groups were evaluated separately. The main results show that “Uninteresting-Interesting” got the lowest score (2.74), and the highest score was “Complex-Simple” (4.67) in the adjective pairs in Balakgazi park by the landscape architects. On the other hand, in architects, “Insufficient Green- Green” (3.19) has the lowest value, while the highest score is “Complex-Simple” (4.48). Landscape architects generally negatively evaluated the adjective pairs. As a result of the EFA, the adjective pairs were grouped under two-factor groups: “Excitement” and “Pleasure and Dominance” according to landscape architects. On the other hand, architects determined two-factor groups: “Excitement and Dominance” and “Excitement”. MANOVA results show that while there was no statistical difference in the determination of the factor groups according to gender and whether participants had seen the Balakgazi park (p>0.05), there were differences in their responses according to their levels of design education (p<0.05).
Keywords: MANOVA; Faktör analizi; Peyzaj algısı; Anlamsal farklılaşım yöntemi